Agglomeration of sub-micron particles by a non-thermal plasma electrostatic precipitator - Vishnu Thonglek (2018)
Non-thermal Plasma agglomeration is presented as a promising process to reduce the number concentration of sub-micron particles in an acrylic duct, which included a saw-tooth electrode and a wire-plate electrostatic precipitator (ESP). The generated plasma by pulse-energized ESP, the particle agglomerations were controlled under operating conditions such as pulse voltages, pulse frequencies, dust loadings, and gas velocities. When gas velocity increased from 0.5 to 1ms-1at 45kVp, 20kHz, it was found that efficiency was increased. At gas velocity of 1ms-1, the sub-micron particle number reduction efficiency for all particle sizes was over 90% in ESP. © 2013 Elsevier B.V.